2022
DOI: 10.3389/fphar.2022.812338
|View full text |Cite
|
Sign up to set email alerts
|

Ontology-Based Classification and Analysis of Adverse Events Associated With the Usage of Chloroquine and Hydroxychloroquine

Abstract: Multiple methodologies have been developed to identify and predict adverse events (AEs); however, many of these methods do not consider how patient population characteristics, such as diseases, age, and gender, affect AEs seen. In this study, we evaluated the utility of collecting and analyzing AE data related to hydroxychloroquine (HCQ) and chloroquine (CQ) from US Prescribing Information (USPIs, also called drug product labels or package inserts), the FDA Adverse Event Reporting System (FAERS), and peer-revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…In our study, a number of expected ADE signals on the PT level were observed such as "creatinine renal clearance decreased" (95% CI of PRR = 137.80 ± 4.17) and "liver function test increased" (95% CI of PRR = 29.84 ± 1.23) of remdesivir, "acute generalized exanthematous pustulosis" (95% CI of PRR = 46.53 ± 1.77) and "torsade de pointes" (95% CI of PRR = 33.68 ± 1.62) of hydroxychloroquine, and "ventricular arrhythmia" (95% CI of PRR = 30.27 ± 2.43) and "cardiovascular insufficiency" (95% CI of PRR = 22.07 ± 2.28) of azithromycin (Drugs.com, 2021). Some of these signals were also consistent to other data mining research studies conducted before (Gérard et al, 2021;Ngai et al, 2022). In addition, for azithromycin and remdesivir, we noticed that all the top 3 signals are associated with the heart and liver.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, a number of expected ADE signals on the PT level were observed such as "creatinine renal clearance decreased" (95% CI of PRR = 137.80 ± 4.17) and "liver function test increased" (95% CI of PRR = 29.84 ± 1.23) of remdesivir, "acute generalized exanthematous pustulosis" (95% CI of PRR = 46.53 ± 1.77) and "torsade de pointes" (95% CI of PRR = 33.68 ± 1.62) of hydroxychloroquine, and "ventricular arrhythmia" (95% CI of PRR = 30.27 ± 2.43) and "cardiovascular insufficiency" (95% CI of PRR = 22.07 ± 2.28) of azithromycin (Drugs.com, 2021). Some of these signals were also consistent to other data mining research studies conducted before (Gérard et al, 2021;Ngai et al, 2022). In addition, for azithromycin and remdesivir, we noticed that all the top 3 signals are associated with the heart and liver.…”
Section: Discussionsupporting
confidence: 90%
“…Some data mining works also have been performed trying to figure out some meaningful signals. However, these works focused either only on some certain ADEs or only on some certain kinds of medicines ( Ngai et al, 2022 ; Wu et al, 2022 ; Zhao et al, 2022 ). Hence, a work providing a whole picture based on the FAERS might be imperative and more helpful.…”
Section: Discussionmentioning
confidence: 99%
“…Enriched (i.e., statistically significant) MedDRA terms from VAERS data analysis can be mapped to the OAE terms, which can be further analyzed using the more accurate OAE AE classification. Multiple studies have shown that the method of the MedDRA-OAE term mapping followed by OAE-based AE classification enables valuable AE classification and data analysis (Sarntivijai et al, 2012;Xie et al, 2016a;Xie et al, 2016b;Wang et al, 2017;Xie et al, 2018;Ngai et al, 2022).…”
Section: Introductionmentioning
confidence: 99%